TGFβ Controls CCN3 Expression in Nucleus Pulposus Cells of the Intervertebral Disc - Tran, Cassie M. (2011)
OBJECTIVE: To investigate TGFβ regulation of CCN3 expression in cells of the nucleus pulposus. METHODS: Real Time RT-PCR and Western blot analysis was used to measure CCN3 expression in the nucleus pulposus. Transfections were used to measure the effect of Smad3, MAPKs and AP1 on TGFβ mediated CCN3 promoter activity. Lentiviral knock down of Smad3 was performed to asses the role of Smad3 in CCN3 expression. RESULTS: CCN3 was expressed in embryonic and adult intervertebral discs. TGFβ decreased CCN3 expression and suppressed its promoter activity in nucleus pulposus cells. DN-Smad3, Smad3-siRNA or DN-AP1 had little effect on TGFβ suppression of CCN3 promoter activity. However, p38 and ERK inhibitors blocked suppression of CCN3 by TGFβ, suggesting involvement of these signaling pathways in the regulation. Interestingly, overexpression of Smad3, in absence of TGFβ increased CCN3 promoter activity. We validated the role of Smad3 in controlling CCN3 expression in Smad3 null mice and in nucleus pulposus cells transduced with lentiviral shSmad3. In terms of function, treatment with rCCN3 showed a dose dependent decrease in proliferation of nucleus pulposus cells. Moreover, CCN3 treated cells shows a decrease in aggrecan, versican, CCN2 as well as collagen type I expression. CONCLUSION: The opposing effect of TGFβ on CCN2 and CCN3 expression and suppression of CCN2 by CCN3 in nucleus pulposus cells furthers the paradigm that these CCN proteins form an interacting triad, possibly important in maintaining extracellular matrix homeostasis and cell number.